Power and Positionality: Negotiating Insider/Outsider Status in Multicultural and Cross-Cultural Research - Sharan Merriam; Gabo Ntseane; Ming-Yeh Lee; Youngwha Kee; Juanita Johnson-Bailey; Mazanah Muhamad (Adult Education Research Conference, 2000)
No abstract available.